(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Karmayoga is a path of liberation given in Bhagavad Gita. Karmayoga means a path of liberation through selfless actions. Selfless actions are those which are free from desire of fruit (success or failure). But the main aspect of karamayoga is that what types of karma one should do and which types of karma one should not do in life that he can follow the path of karmayoga. In Hinduism there is the concept of ‘Dharma’ which is very important part of karmayoga. ‘Dharma’ explain that which karma are suitable for karmayoga that leads to satisfaction, peace at mind and harmony of society. So karma according to ‘dharma’ are only those karma that opens the path of libderation through action (karmayoga).